Divergent subgenome evolution in the allotetraploid frog Xenopus calcaratus - Knytl, Martin; Fornaini, Nicola R; Bergelová, Barbora; Gvoždík, Václav; Černohorská, Halina; Kubíčková, Svatava; Fokam, Eric B; Evans, Ben J; Krylov, Vladimír (Gene, 2023)
Allopolyploid genomes are divided into compartments called subgenomes that are derived from lower ploidy ancestors. In African clawed frogs of the subgenus Xenopus (genus Xenopus), allotetraploid species have two subgenomes (L and S) with morphologically distinct homoeologous chromosomes. In allotetraploid species of the sister subgenus Silurana, independently evolved subgenomes also exist, but their cytogenetics has not been investigated in detail. We used a diverse suite of cytogenetic and molecular FISH techniques on an allotetraploid species in Silurana-Xenopus calcaratus-to explore evolutionary dynamics of chromosome morphology and rearrangements. We find that the subgenomes of X. calcaratus have distinctive characteristics, with a more conserved a-subgenome resembling the closely related genome of the diploid species X. tropicalis, and a more rapidly evolving b-subgenome having more pronounced changes in chromosome structure, including diverged heterochromatic blocks, repetitive sequences, and deletion of a nucleolar secondary constriction. Based on these cytogenetic differences, we propose a chromosome nomenclature for X. calcaratus that may apply to other allotetraploids in subgenus Silurana, depending on as yet unresolved details of their evolutionary origins. These findings highlight the potential for large-scale asymmetry in subgenome evolution following allopolyploidization.
Keywords: molekulární evoluce; Chromosomes; Xenopus laevis; Chromosome; Evolution, Molecular; genom; Genome; Xenopus; zvířata; Genome, Plant; Chromosome length; Cytogenetics; Allopolyploidization; Diploidy; chromozomy; Animals; genom rostlinný; FISH; diploidie